Analysis of Driving Data of Lorries on a Certain Route - Czégé, Levente; Vámosi, Attila; Kocsis, Imre (International Journal of Engineering and Management Sciences, 2020)
In this paper the development of a driving cycle for lorries traveling a certain route is presented. A typical transportation route has been selected, which used by lorries instrumented with the proper data-collecting equipment. We used these on-board units to collect data over a long time period in the real-life traffic. We filtered the collected data, and carried out a statistical evaluation on the basis of the measured data.